Perlindungan Hukum Bagi Pengguna Angkutan Ojek Berbasis Aplikasi Online Sesuai Dengan Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan - Husni Thamrin; Manar Dimansyah (LPPM STIH Awang Long, 2022)
The development of online motorcycle taxis has been very fast lately because it is accompanied by millennials who are very dominant in liking this new transportation. Indonesia could be one of the world's examples of transportation with the help of this digital cellphone. However, to be an example, of course, it needs really in-depth arrangement and research so that it can run and develop according to the needs desired by the community. Many problems experienced by this online transportation. But there is no problem that cannot be overcome with experience and through it. Therefore, educated people are needed to research more deeply and find solutions. The right one for that. Currently, there are 2 of the most popular online motorcycle taxis in Indonesia, namely Go-Jek and Grab, and it is likely that in the future the newest competitors will emerge thanks to people's preference for this new style of transportation. Here the author wants to convey the form of legal protection that this online-based application can provide to the public. The author uses the library research method or literature review.